Atypical Molluscum Contagiosum Mimicking Cutaneous Warts in an HIV Patient - Hidayat, Deriel Elka; Setyowatie, Lita; Widiatmoko, Arif; Murlistyarini, Sinta; Retnani, Diah Prabawati (Journal of Pakistan Association of Dermatologists, 2025)
Molluscum contagiosum (MC) is clinically characterized by small, dome-shaped, pearly-white to skin-colored papules and a self-limiting course. MC may present in several atypical morphologies which mimicking other dermatoses, especially on an immunocompromised patients. The lesions are usually extensive and cause disfigurement when associated with HIV. The terminology of “agminated” MC describes the dense grouping of several MC lesions. The aim of this case report is to report the agminated MC which mimicking a cutaneous wart of an HIV patient. A 36-year-old married woman with HIV complained of multiple red bumps that were initially pea-sized and gradually increased in size and number. The lesion spread over the face, armpits, hands, thighs, genital area, and feet for 9 months. History indurated, painless, and ulcerative chancre was denied. There was no history of blood transfusion, trauma, or any drug intake before the appearance of these lesions. There were no such lesions present on her husband. There was no history regarding the HIV status of the husband. Her CD4 absolute count was 61 cells/mm and serological testing for syphilis was non-reactive. Based on the findings, the patient was diagnosed with atypical MC and planned to have cryosurgery. Unfortunately the patient was loss control to follow up. Awareness among clinicians regarding the atypical presentations of MC is of paramount importance in the early diagnosis and management of this contagious disease. Rarely, atypical presentations of MC have been described in immunocompromised patients. Dermoscopy and histopathological examination is needed to determine the diagnosis of these atypical MC.